La critique de la doctrine de l'abstraction de Jacques de Viterbe - Côté, Antoine (Université d'Ottawa | University of Ottawa, 2013)
The paper examines the Augustinian Hermit James of Viterbo’s critique of abstraction theory as an account of the origin of intellectual knowledge. It then examines the details of James’ own preferred solution to the problem of knowledge acquisition, which is based on the idea that the intellect possesses the seeds of all the particular items of knowledge it will ever acquire. Finally, the paper brings to light and then discusses some of the difficulties James encounters in trying to provide a consistent innatist account of knowledge.
Keywords: abstraction; cognition; innatism